Association between cagemate number and risk of death in mice: a time-varying covariate analysis using Cox frailty models - Thirupathi R. Mokalla; Erik S. Parker; Daniel L. Smith; Luis-Enrique Becerra-Garcia; Olivia C. Robertson; Deependra K. Thapa; Mounika Kandukuri; Bret M. Rust; David B. Allison (GeroScience, 2026)
Social housing is desirable for the health and well-being of laboratory mice, as social interactions with conspecifics influence both behavioral and physiological outcomes. Although group housing benefits social species, it can introduce variability in mortality outcomes, and raise welfare concerns, particularly with the emergence of aggression or fluctuating cage densities. Despite this, few studies have evaluated how changes in the number of living cagemates over time are associated with survival, particularly in a sex-specific manner. We analyzed data from the National Institute on Aging’s Interventions Testing Program (ITP; n = 2635 UM-HET3 mice), across three research sites to assess whether housing density influenced longevity differently in male and female mice. Mice were housed in same-sex cages (median = 3 per cage) without reassignment after cagemate death. We applied Cox frailty models incorporating nested random effects for cage and site, with fixed effects for sex, treatment, and time-varying number of living cagemates to estimate hazard ratios, which allowed us to assess the instantaneous risk of death associated with changes in cagemate number. Results showed a significant main effect of the number of living cagemates on mortality and a significant interaction between sex and cagemate count, indicating sex-specific responses. Female mice exhibited a pronounced increase in mortality rate as cage density declined, suggesting a potential role of social buffering in longevity. These findings emphasize the importance of considering social housing dynamics, particularly for female mice, in both experimental design and animal welfare protocols. Graphical Abstract